FRI0287 Incidence of lupus nephritis and 18-month follow up in colombian patients with systemic lupus erythematosus. (15th June 2017) - Alzate, MA; Hernandez-Parra, D; Salazar-Uribe, JC; Ortiz-Salazar, P; Pineda, R; ,
Abstract : Background: Lupus nephritis (LN) is one of the major indicators of poor prognosis in patients with systemic lupus erythematosus (SLE). Multiple studies with Latin-American SLE population have shown a higher prevalence of LN, higher severity, and less favorable outcomes (1). Objectives: To determine the incidence of lupus nephritis and end-stage renal failure, as well as evaluate progression of renal function and proteinuria during an 18-month follow up in colombian patients with SLE. Methods: A retrospective cohort study was conducted in 1448 patients with SLE, 41 of which were diagnosed with LN between August/2014 and July/2015. Follow up was made for 18 months, analyzing glomerular filtration rate (GFR) and proteinuria, induction and manteinance therapy, renal relapses, hospitalizations and mortality. Univariate analysis was done to describe sociodemographic and clinical variables. Longitudinal data analysis was performed using linear mixed models with random intercepts. In all cases, a p value <0.05 was considered statistically significant. Results: Clinical characteristics of patients with LN are shown in table 1 . Eighty-five percent of LNs where biopsy-proven. Incidence of LN was 2, 83 cases/100 SLE patients/year. The incidence of end-stage renal failure was 7, 31 cases/100 LN patients. During the 18-month follow up, 34% of patients had hospitalizations related to SLE activity or complications, 7, 3% renal relapse, 2, 4% rebiopsy, and no mortality cases. Induction therapy was done with cyclophosphamide in 58, 5% and with mycophenolate mofetil in 41, 4%, with 30% of the patients requiring re-induction therapy, Ten percent of patients required use of rituximab due to refractory response to multiple treatments. In longitudinal linear analyses, age at diagnosis and anti dsDNA was positively associated to GFR variations (Figure 1, A), while anti Sm, hematologic involvement and biopsy classification were associated to proteinuria variations during time of follow-up (Figure 1, B). Conclusions: In a real life scenario, anual incidence of lupus nephritis was 2, 83 cases/100 SLE patients. A high proportion of patients with refractory response to multiple immunomodulatory treatments for LN were identified. References: Pons-Estel GJ, Catoggio LJ, Cardiel MH, Bonfa E, Caeiro F, Sato E, et al. Lupus in Latin-American patients: lessons from the GLADEL cohort. Lupus. 2015;24(6):536–45. Disclosure of Interest: None declared